EFFECT OF PROTEIN MALNUTRITION ON THE WEIGHT AND SERUM ALBUMIN OF ALBINO RATS - Qureshi, Muhammad Imran; Qureshi, Zaheeruddin (Journal of Ayub Medical College Abbottabad, 2001)
Background: Protein Malnutrition is one of the major mortality factors in the children of Pakistan. Not only do the children suffer from infections (because of low resistance secondary to malnutrition), but they also lose weight significantly. The two spectra of the diseases are Kwashiorkor and Marasmus. We conducted this study on laboratory’ animals to assess the weight change and correlated it with the extent of malnutrition by studying and estimating the serum albumin levels as well. Methods: 40 male albino rats of 2 weeks’ age were used for the experiment. They were divided into Control and Experimental groups containing equal number of animals. The experimental group was subjected to protein malnutrition for 3 to 6 weeks. They were killed with the paired control animals. The parameters of the two groups were compared for statistical analysis. Results: The results showed significant change in the weights of the experimental animals right from the first week of malnutrition while the change in serum albumin level became significant after prolonged malnutrition. Conclusion: Protein malnutrition is reflected from the decrease in the serum albumin levels of the animals and their weights are also decreased significantly.